Current Strategies on the Enantioselective Synthesis of Modified Nucleosides - Mondal, Samir Kumar; Mahto, Birkishore; Pal, Shantanu; Chandra, Girish (Synlett, 2024)
The isolation of two carbocyclic nucleosides, viz., neplanocin A and aristeromycin, from natural sources, triggered a revolution in the scientific community, leading to the development of more versatile and therapeutically useful compounds. For this purpose, many new methods for the synthesis of the carbocyclic framework of nucleosides have been developed. These efforts resulted in the successful development of many marketable drugs. The inherent benefits associated with carbocyclic nucleosides, such as higher lipophilicity and metabolic stability, resistance against glycosidic hydrolysis and the ability to modify aromatic bases by cellular phosphorylases, make them popular for the development of drugs against cancer and different viruses. Classically, carbocyclic nucleosides of various ring sizes and configurations have been synthesized starting from chiral pool substrates, such as ribose, glucose, etc., but recently, many other new asymmetric versions have been developed. Herein, we present recent developments on the catalytic enantioselective synthesis of nucleoside analogues, including carbocyclic and other varieties. This account provides new insights into the future development of modified nucleosides.1 Introduction2 Cyclic Nucleosides3 Acyclic Nucleosides4 Conclusion
Keywords: nucleosides; asymmetric synthesis; enantioselectivity; diastereoselectivity; carbocyclic nucleosides; asymmetric catalysis